2009
DOI: 10.1007/s00467-009-1151-8
|View full text |Cite
|
Sign up to set email alerts
|

The value of sequential dialysis, mannitol and midodrine in managing children prone to dialysis failure

Abstract: The uremic state impairs compensatory responses to ultrafiltration (UF). Intradialytic symptoms and hypotension can result and lead to premature discontinuation of treatment and sub-optimal dialysis. We report the benefits of mannitol, sequential dialysis and midodrine in reducing dialysis failures in those children prone to intradialytic hypotension. Prophylactic mannitol halved the odds of intradialytic symptoms and hypotension and increased UF volumes. Sequential dialysis halved the odds of symptoms but hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In another study of six pediatric patients prone to IDH (mean age 12 years), Hothi et al. reported that the use of mannitol vs not was associated with a 56% reduction in the frequency of intra‐dialytic symptoms (abdominal pain, cramps, headaches, loss of consciousness or change in behavior), with similar findings from a prospective review of 506 treatments from 10 patients . Furthermore, Battaglia et al.…”
Section: Interventions To Minimize Intra‐dialytic Osmolality Declinementioning
confidence: 72%
“…In another study of six pediatric patients prone to IDH (mean age 12 years), Hothi et al. reported that the use of mannitol vs not was associated with a 56% reduction in the frequency of intra‐dialytic symptoms (abdominal pain, cramps, headaches, loss of consciousness or change in behavior), with similar findings from a prospective review of 506 treatments from 10 patients . Furthermore, Battaglia et al.…”
Section: Interventions To Minimize Intra‐dialytic Osmolality Declinementioning
confidence: 72%
“…A cut-off of 7.5 mg of the total dose was applied for a 3 h treatment and no midodrine was given in the final 30 min irrespective of BP. Used within this context, we observed a 10-to 15 mmHg increase in the systolic BP within 30 min of administering midodrine in the absence of adverse effects in the intradialytic or interdialytic period [72]. Despite the success, owing to the limited paediatric experience we can only recommend midodrine for resistant cases.…”
Section: Intradialytic Midodrinementioning
confidence: 91%
“…Adult data-variable results [82] Paediatric data-positive effect [72] Quotidian haemodialysis Paediatric data-improved haemodynamic stability [83] move from the interstitial space to the vascular compartment. In addition, owing to a concentration gradient, sodium diffuses across the dialyser membrane, transferring a sodium load to the patient and thus with it the risk of causing interdialytic thirst, increased interdialytic weight gain and hypertension.…”
Section: Bicarbonate Buffersmentioning
confidence: 97%
See 2 more Smart Citations